Mengukur Kadar Gula Darah Menggunakan Aplikasi Alat Pengukur Kadar Gula Darah Berbasis Dekstop Sebagai Langkah Awal Untuk Mencegah Diabetes: Literatur Review - Duta Ficky Arif Mukmin; Kalam Badruz Zaman (STIKes Ibnu Sina Ajibarang, 2024)
Indonesia is the sixth largest country with diabetes in the world. Of the total, most people make rice as a staple food so that many people suffer from diabetes due to irregular eating patterns and lack of exercise. This review article is an overview of the importance of maintaining blood sugar levels. It is hoped that maintaining blood sugar levels can be started from a small-scale community so that it can reduce diabetes sufferers in Indonesia.